Le paysage industriel sous le prisme de l'art contemporain. Le cas de la fondation Pirelli HangarBicocca - Valeria Giudici (Bulletin de l’Association de Géographes Français)
This article examines how the territorial dimension is integrated into the activities of a corporate foundation for contemporary art. It focuses on the Pirelli HangarBicocca foundation, located in the post-industrial Bicocca district of Milan, exploring the theme of valorizing an industrial building that has been preserved from trivialization. After describing the cultural elements of the Bicocca landscape linked to the historical presence of the Pirelli company and examining the perception of the foundation's building by local actors, the article presents some examples of artistic interventions in the space of the cultural institution. These practices show how the interpretation of industrial spaces through the medium of art helps to strengthen the integration of the territorial dimension into the company's identity, while at the same time enhancing and bringing up to date the industrial landscape of the Milanese district. The analysis suggests that the foundation is more open and accessible thanks to its reflection on the territorial context, counteracting the elitist character generally associated with contemporary art and private institutions.